Sheehan syndrome with Gitelman syndrome, Tackling Additive Morbidity (Iranian Journal of Kidney Diseases, 2019)
Sheehan syndrome (SS) is postpartum hypopituitarism resulting from pituitary gland necrosis caused by severe hypotension due to massive intra or post-partum hemorrhage. Defective NaCl transport in the distal convoluted tubule, due to mutations affecting the thiazide sensitive Na-Cl-cotransporter results in the autosomal recessive salt-losing renal tubulopathy, Gitelman syndrome (GS). These two have been rarely described together. We report the case of a middle-aged woman with both these conditions, resulting in management issues. Physicians encountering unexplained hypokalemia refractory to standard management must consider the possibility of renal tubular disorders.